Development Of Branch System Of Certification Of Software And Information Means Of Scientific And Educational Purpose - Sergeev, Ю.С. (Journal of Information Technologies in Education (ITE), 2009)
Object of scientific and research job is the branch system of certification of software and information means and databases of scientific and educational purpose of the Ministry of Education and Science of Ukraine. The job overall objective - to develop and producing constantly operating system of certification of software, information means and databases of scientific and educational purpose which are acquired, purchased, developed, supplied, delivered and maintained in a field of activity of the Ministry of Education and Science of Ukraine. As a result of performance of the first stage documents of a first stage standard - methodical maintenance of branch system of certification are developed.